ADVANTAGES AND DISADVANTAGES OF X-RAY DIAGNOSIS FOR WHOOPING COUGH PATIENTS - Stevanović, Kristina; Radovanović, Jovana (HEALTH CARE, 2025)
The World Health Organization describes whooping cough as "a highly contagious disease of the respiratory tract caused by Bordetella pertussis," a microorganism specifically pathogenic to humans. Whooping cough affects all ages, especially children, and is one of the leading causes of death in children under one year of age. Incubation usually lasts 7 to 10 days, and the clinical picture depends on age and vaccination status. Whooping cough is often a challenge because of symptoms that are similar to those of other respiratory infections. In adults, the disease is usually asymptomatic mild symptomatic infection occurs, especially in the elderly who have been previously vaccinated. However, in children under 5 years of age, especially infants, the clinical picture is more severe. It is in the form of paroxysmal cough, which may be accompanied by characteristic wheezing or inspiratory whooping and vomiting or expelling a small amount of sticky mucus. Dyspnea, cyanosis and apnea. can also occur, especially in infants. The most common complication in unvaccinated children is bronchopneumonia. In order to diagnose the disease, in addition to the specific clinical picture, a nasopharyngeal swab or aspirate is most often used for PCR testing or bacterial cultivation and blood for serological analyses. X-ray of the lungs in persons with suspicion of whooping cough can play a significant role in the assessment of complications and differential diagnosis, and in children under four years of age, also in establishing the diagnosis. However, during chest X-ray imaging, coughing attacks during imaging, inability to detect the disease in the early stages, exposure of the patient to ionizing radiation, and errors in the interpretation of images may occure.